Kajian Faktor yang Mempengaruhi Pendapatan Petani Hortikultura Buahan Sistem Dusung di Kota Ambon Provinsi Maluku 2022 - Junus, Mursal; Sumiratin, Endang (Jurnal Ilmiah Dikdaya, 2022)
Horticultural production in the context of sustainable agriculture if it is managed optimally with local characteristics, from an income standpoint, it will have an effect on reducing poverty and providing employment, especially in rural areas as the basis for the highest poverty dominance. The purpose of this study was to analyze the potential income of fruit horticulture and the factors that influence the income of fruit horticulture farmers in the Dusung system in Ambon City. The research was conducted in 2014 at horticulture production centers in Hutumuri Village in South Leitimur District, Soya Village in Sirimau District and Hative Besar Village in Teluk Ambon District with a total sample of 88 farmers. The analysis used was multiple linear regression analysis and t test (Î± 0.05 %) for the significance of each variable. The results showed that the variables of land area, number of mangosteen trees, number of clove trees, number of durian trees partially had a significant effect on income received with a positive coefficient direction. While the age variable has a significant effect on income received with a negative coefficient direction. The largest fruit horticulture income is commodity types of mangosteen, salak, duku, nutmeg, durian and cloves. Of the total existing commodities, soya hamlet has the largest income level of 107,732 (Rp million/year), then Hutumry and Hative Besar hamlets respectively 74,795 (Rp million/year) and 70,147 (Rp million/year) with an average income of the three hamlets amounted to 84,229 (Rp million/year).